A cheap, high-performance hard carbon anode material for sodium-ion secondary batteries
By carbonizing waste wood and chemical vapor deposition, a hard carbon anode material with high specific capacity and excellent cycle performance was prepared, which solved the problems of low energy density and poor cycle stability of hard carbon anode materials in sodium-ion secondary batteries. question.
Patent Information
- Application Number
- CN202411288159.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-14
AI Technical Summary
The problems of hard carbon anode material in sodium ion secondary batteries are low energy density, low first-time Coulomb efficiency, low capacity and poor cycle stability.
By regulating abandoned wood for carbonization preparation and chemical gas phase deposition, it is prepared to prepare hard carbon negative materials with rich microporous structures and pseudo graphite -like structures. This material optimizes the pore distribution and carbon layer structure through the possibility and regulating temperature and temperature change rate, and improves the insertion capacity and storage efficiency of sodium ions.
It significantly improves the ratio capacity of hard carbon negative materials, the first Kuron efficiency and circulation performance of the first, and the electrochemical performance is better than the general commercial hard carbon, and it is suitable for large -scale industrial production.
Smart Images

Figure CN118811800B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a sodium ion battery negative electrode material, and more specifically, it relates to a cheap, high-performance sodium ion secondary battery hard carbon negative electrode material. Background Art
[0002] As lithium resources are limited and most of them are distributed in South America, Australia and other regions, the supply chain is vulnerable to international market fluctuations, and mining will cause ecological damage and pollution. In this case, sodium-ion secondary batteries, as a substitute and supplement to lithium-ion secondary batteries, have many economic and environmental advantages and are the most promising alternative to lithium-ion batteries in the field of energy storage.
[0003] At present, there are many positive electrode materials for sodium-ion secondary batteries, but there is no mature solution for negative electrode materials. Take graphite as the negative electrode material for lithium-ion secondary batteries. It has a relatively ordered layered structure, and lithium ions can be inserted into the graphite layer and stored in this way. However, the radius of sodium ions is much larger than that of lithium ions, so their electrochemical kinetic performance is not as good as that of lithium ions, and they cannot be intercalated between graphite layers, making low-cost graphite unable to be used as the negative electrode material for sodium-ion batteries.
[0004] Hard carbon materials solve this problem. Hard carbon materials have the advantages of abundant sources, simple preparation, and low cost. Their microstructures consist of pseudo-graphite nanodomains and amorphous nanoregions with several arbitrary orientations, distortions, and wrinkles. They have a large number of edges or defects, gaps, and pores with various morphological characteristics. However, hard carbon as a negative electrode material for sodium-ion secondary batteries has problems such as low first coulombic efficiency, low capacity, and poor cycle stability, which leads to low energy density of sodium-ion batteries and limits the development of hard carbon negative electrodes.
[0005] In order to solve the problems existing in the current hard carbon negative electrode, it is necessary to provide a hard carbon negative electrode with low cost, high first coulombic efficiency, high specific capacity and good cycle stability, improve the energy density of the hard carbon negative electrode material, and accelerate the commercial development of sodium ion batteries. Summary of the invention
[0006] In order to solve the problem of low energy density of hard carbon negative electrode materials, the present application provides a cheap, high-performance hard carbon negative electrode material for sodium ion secondary batteries.
[0007] The present application provides a cheap, high-performance hard carbon negative electrode material for sodium ion secondary batteries, wherein the negative electrode material is waste wood that has been carbonized and regulated by chemical vapor deposition. The preparation process of the negative electrode material includes the following steps:
[0008] S1. Washing, drying, crushing and screening the waste wood to obtain a clean precursor;
[0009] S2. performing low temperature pyrolysis pretreatment on the clean precursor to obtain a pretreated precursor;
[0010] S3. The pretreated precursor is washed and dried to obtain a clean pretreated precursor;
[0011] S4. Carbonization preparation: The clean pretreated precursor prepared in S3 is placed in a high temperature tube furnace for high temperature calcination, a protective gas is introduced, the temperature is gradually raised to the final temperature, and then the reaction is carried out at a constant temperature. After the reaction is completed, the temperature is gradually lowered to room temperature to obtain a high temperature calcined precursor;
[0012] S5. Chemical vapor deposition: Place the high-temperature calcined precursor into a rotary tube furnace, introduce a protective gas, gradually raise the temperature to a specific temperature, introduce a highly reactive gas, then stop introducing the reactive gas, react at a constant temperature, and gradually cool down to room temperature after the reaction to obtain a hard carbon negative electrode material.
[0013] By adopting the above scheme, the obtained negative electrode material has more microporous structures, more pseudo-graphite layered structures, and rich defects. The chemical vapor deposition method is used to control and improve the composition and structure of waste wood-derived hard carbon, construct closed pores to reduce the irreversible adsorption of sodium ions, and change the pseudo-graphite interlayer spacing to facilitate sodium ion intercalation, inhibiting the irreversible reaction caused by the organic solvent molecules in the electrolyte entering the internal micropores; at the same time, optimizing the internal pore size can also increase the reversible sodium storage sites, thereby improving the first coulombic efficiency and specific capacity of the hard carbon negative electrode material.
[0014] The waste wood used can preferably be one or more of completely discarded rubber wood and beech wood. The raw material cost is low. The waste wood precursor can also increase the specific surface area of the porous carbon material, which is beneficial to increase the low potential platform capacity of the hard carbon negative electrode. The above preparation steps are simple to operate, the process is clean, and it is suitable for large-scale industrial production. The prepared negative electrode material has high specific capacity, high first coulomb efficiency, excellent cycle performance, and electrochemical performance is better than general commercial hard carbon.
[0015] In a specific possible implementation scheme, the preparation step of low temperature cracking in S2 includes: placing the clean precursor into a high temperature tubular furnace for calcination, introducing a protective gas, gradually heating up to the final temperature, then reacting at a constant temperature, and gradually cooling down to room temperature after the reaction is completed.
[0016] By adopting the above scheme, inorganic impurities can be effectively removed, particle size can be improved, and the consistency of performance of biomass-derived hard carbon materials can be improved. The obtained negative electrode material has abundant internal micropores and mesopores, the volume of the negative electrode material is more stable during the sodium ion extraction and embedding process, the battery capacity is high, and the cycle performance is good.
[0017] In a specific embodiment, the temperature in the preparation step of low temperature cracking in S2 is first increased to 250-350°C at a rate of 0.5-10°C / min, then increased to a final temperature of 500-800°C at 0.5-4°C / min, the constant temperature time is 0.5-8h, and the cooling rate is 0.1-10°C / min.
[0018] By adopting the above scheme, the temperature, time, heating and cooling rates of the low-temperature pyrolysis process are controlled, the structure of the waste wood precursor is further optimized, a transmission channel is provided for the insertion of sodium ions, and the platform capacity is increased.
[0019] In a specific embodiment, the protective gas in the preparation step of low temperature cracking in S2 includes one or more of argon or nitrogen, and the flow rate of the protective gas is 10-100 mL / min.
[0020] By adopting the above scheme, the protection effect of the low-temperature cracking process is good, the flow rate of the protective gas is small and the cost can be controlled, the heating and cooling rates are stable, and the structure of the obtained negative electrode material is uniform, stable and not easy to be distorted.
[0021] In a specific embodiment, the cleaning is an acid wash with a concentration of 0.2-2 M, and the acid comprises one or more of hydrochloric acid, nitric acid, and sulfuric acid.
[0022] By adopting the above scheme, the residual inorganic impurities after cracking are removed, eliminating interference without destroying the structure of the negative electrode material.
[0023] In a specific implementation scheme, the heating rate in S4 is 0.5-10°C / min, the final temperature is 700-1600°C, the constant temperature time is 0.5-8 h, and the cooling rate is 0.1-10°C / min.
[0024] By adopting the above scheme, the heating rate is fast, the graphitization degree of the obtained hard carbon material is good, the interlayer spacing of the pseudo-graphite layers is appropriate, and the setting of the final temperature will cause the open pores to shrink into closed pores, increase the reversible sodium storage sites, and the obtained negative electrode material has good cycle performance.
[0025] In a specific embodiment, the protective gas in S4 includes one or more of argon or nitrogen, and the flow rate of the protective gas is 10-100 mL / min.
[0026] By adopting the above scheme, the flow rate of the protective gas is limited, the pore structure of the obtained negative electrode material is further improved, the number of closed pores is increased, and the reversible capacity is improved.
[0027] In a specific embodiment, the highly reactive gas in S5 is acetylene with a flow rate of 28-100 mL / min, and the protective gas includes one or more of argon or nitrogen with a flow rate of 28-100 mL / min.
[0028] By adopting the above scheme, the waste wood source derived hard carbon is subjected to chemical vapor deposition, which has good protection effect and deposition effect, and the surface of the hard carbon negative electrode material obtained has a dense and uniform carbon coating layer with richer pores.
[0029] In a specific implementation scheme, the heating rate in S5 is 5-10°C / min, the final temperature is 700-900°C, the time for introducing highly reactive gas is 0.5-2h, the constant temperature time is 0.4-6h, and the cooling rate is 5-10°C / min.
[0030] By adopting the above scheme, chemical vapor deposition has a good effect on regulating the structure of the prepared hard carbon negative electrode material, and a dense carbon coating layer is stably deposited on the surface of the prepared hard carbon negative electrode material.
[0031] In a specific possible implementation scheme, S3 also includes the following steps: mixing polyvinyl alcohol, butanediol, glycerol, sulfonate polyether diol, sodium dodecylbenzene sulfonate, and deionized water, stirring evenly, then adding sodium bicarbonate and sodium bicarbonate microcapsules, stirring evenly to obtain a mixture, adding the mixture and polyvinyl alcohol fibers to a coating machine to obtain sodium bicarbonate-coated polyvinyl alcohol fibers; electrostatically spraying the obtained sodium bicarbonate-coated polyvinyl alcohol fibers on the clean pretreatment precursor, and drying.
[0032] Due to the hindrance of the macromolecular cross-linking structure inside the carbon layer, the carbon layer in the hard carbon cannot extend infinitely. It usually presents a carbon layer stacking structure in the short range and a disordered state in the long range. By adopting the above scheme, sodium bicarbonate and sodium bicarbonate microcapsules are relatively simply coated on the polyvinyl alcohol fiber and evenly distributed on the surface of the clean pretreatment precursor prepared by S3. Sodium bicarbonate spans the long-range carbon layer on the surface of the clean pretreatment precursor through the fibrous polyvinyl alcohol. The sodium bicarbonate-coated polyvinyl alcohol fiber decomposes during the subsequent high-temperature calcination, leaving no residual impurities while leaving micropores spanning the long-range carbon layer for the hard carbon material, further adjusting the structure of the surface of the clean pretreatment precursor; through electrostatic spraying, the sodium bicarbonate-coated polyvinyl alcohol fiber forms a certain orientation during the spraying process, is oriented and arranged on the surface of the clean pretreatment precursor, and leaves micropores in the orientation, further adjusting the long-range structure of the clean pretreatment precursor, so that the carbon coating layer formed on the surface of the clean pretreatment precursor in the subsequent vapor deposition process is more dense and uniform. By limiting the mass fraction of each component in the preparation step of sodium bicarbonate-coated polyvinyl alcohol fiber, the prepared sodium bicarbonate-coated polyvinyl alcohol fiber is suitable for the structure of the clean pretreatment precursor prepared in S3 and the calcination temperature in S4, and the prepared hard carbon negative electrode material has better specific capacity, first coulomb efficiency, and capacity retention rate. By using sodium bicarbonate and sodium bicarbonate microcapsules to prepare a mixture to form a coating of polyvinyl alcohol, the decomposition temperature range of sodium bicarbonate is expanded, the foaming effect is better, and abundant micropores and mesopores are left on the clean pretreatment precursor, optimizing the structure of the prepared hard carbon negative electrode material, and sodium ions can be better diffused and stored.
[0033] Preferably, the preparation steps of the sodium bicarbonate microcapsules include: uniformly mixing sodium bicarbonate, epoxy resin and anhydrous ethanol, adding triethylenetetramine and sodium dodecylbenzene sulfonate, stirring evenly, heating for reaction, filtering, washing and drying.
[0034] Preferably, the mass ratio of sodium bicarbonate to sodium bicarbonate microcapsules in the mixture is 1:(1-2).
[0035] The preferred mass ratio of sodium bicarbonate to sodium bicarbonate microcapsules in the mixture is 1:1.5.
[0036] In summary, this application has the following beneficial effects:
[0037] The hard carbon negative electrode material prepared in this application has the advantage of low cost. The raw materials are completely discarded rubber wood and beech wood. It is low in cost, simple to operate, and has a clean process, which is suitable for large-scale industrial production. The prepared hard carbon negative electrode has a specific capacity of more than 300mAh / g; the first coulomb efficiency is higher than 75%, and it has excellent cycle performance, and the electrochemical performance is better than general commercial hard carbon. It uses discarded wood as a carbon source, and the hard carbon negative electrode material with an optimized structure by chemical vapor deposition has a rich microporous structure.
[0038] The hard carbon negative electrode material prepared in the present application has a uniform and stable pore distribution, rich pore sizes, a large number of micropores and mesopores, and rapid diffusion and storage of sodium ions. After the sodium ions are released and embedded, the volume of the hard carbon negative electrode material is not easy to shrink and expand, and the cycle performance is good.
[0039] In the present application, sodium bicarbonate is sprayed on the surface of a clean pretreated precursor to coat polyvinyl alcohol fibers, and the carbon layer structure on the surface of the clean pretreated precursor is further optimized after pyrolysis to form more pores. At the same time, the optimization of the long-range carbon layer structure makes the subsequent vapor deposition effect better, and the obtained hard carbon negative electrode material has better performance in specific capacity, first coulomb efficiency, and capacity retention rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 : Scanning electron microscope (SEM) image of the hard carbon negative electrode material prepared in Example 1 of the present invention.
[0041] Figure 2 : Transmission electron microscope (TEM) image of the hard carbon negative electrode material prepared in Example 1 of the present invention.
[0042] Figure 3 : Nitrogen adsorption-desorption curve obtained in Example 1 of the present invention.
[0043] Figure 4 : Pore size distribution curve of the hard carbon negative electrode material prepared in Example 1 of the present invention.
[0044] Figure 5 : The first cycle charge and discharge curve of the hard carbon negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0045] Unless otherwise specified, the experimental reagents in the preparation examples, embodiments and comparative examples are all conventional commercial brands or obtained through conventional preparation processes.
[0046] Preparation Example:
[0047] Preparation Example 1: Sodium bicarbonate microcapsules:
[0048] 250g of sodium bicarbonate, 100g of epoxy resin and 200ml of anhydrous ethanol were mixed evenly, and then 30g of 10%wt triethylenetetramine and 30g of 10%wt sodium dodecylbenzene sulfonate were added, stirred evenly, heated at 70°C for 6 hours for reaction, filtered, washed and dried to obtain sodium bicarbonate microcapsules.
[0049] Preparation Example 2: Sodium bicarbonate coated polyvinyl alcohol fiber:
[0050] Mix 60g of polyvinyl alcohol, 40g of butanediol, 60g of glycerol, 3g of sulfonate polyether diol, 5g of sodium dodecylbenzene sulfonate and 800g of deionized water, stir evenly, then add 60g of sodium bicarbonate, stir evenly to obtain a mixture, add the mixture and 500g of polyvinyl alcohol fiber into a coating machine to obtain sodium bicarbonate-coated polyvinyl alcohol fiber.
[0051] Preparation Example 3: Sodium bicarbonate coated polyvinyl alcohol fiber:
[0052] 60 g of polyvinyl alcohol, 40 g of butanediol, 60 g of glycerol, 3 g of sulfonate polyether diol, 5 g of sodium dodecylbenzene sulfonate, and 800 g of deionized water were mixed and stirred evenly, and then 30 g of sodium bicarbonate and 30 g of the sodium bicarbonate microcapsules prepared in Preparation Example 1 were added and stirred evenly to obtain a mixture. The mixture and 500 g of polyvinyl alcohol fiber were added to a coating machine to obtain sodium bicarbonate-coated polyvinyl alcohol fiber.
[0053] Preparation Example 4: Sodium bicarbonate coated polyvinyl alcohol fiber:
[0054] 60 g of polyvinyl alcohol, 40 g of butanediol, 60 g of glycerol, 3 g of sulfonate polyether diol, 5 g of sodium dodecylbenzene sulfonate, and 800 g of deionized water were mixed and stirred evenly, and then 24 g of sodium bicarbonate and 36 g of the sodium bicarbonate microcapsules prepared in Preparation Example 1 were added and stirred evenly to obtain a mixture. The mixture and 500 g of polyvinyl alcohol fiber were added to a coating machine to obtain sodium bicarbonate-coated polyvinyl alcohol fiber. Example Example 1
[0055] S1. The waste beech wood is cleaned, dried, crushed and sieved to obtain a pre-treated precursor;
[0056] S2. The obtained pre-treated precursor was placed in a tubular furnace for low-temperature pyrolysis pre-treatment, and a protective gas argon gas with a flow rate of 60 mL / min was introduced, and the temperature was increased to 300 °C at a heating rate of 5 °C / min, and then the temperature was increased to a final temperature of 600 °C at a rate of 1 °C / min. After isothermal reaction for 2 hours, the temperature was cooled to room temperature at a cooling rate of 5 °C / min to obtain a pre-treated precursor;
[0057] S3. Soak the pretreated precursor in 1M / L hydrochloric acid solution for 24 hours, then wash with deionized water until the pH is 7, and finally dry it in a vacuum oven to obtain a clean pretreated precursor.
[0058] S4. The clean pretreated precursor was placed in a high-temperature tube furnace for high-temperature calcination, and a protective gas argon gas was introduced at a flow rate of 60 mL / min. The temperature was increased to a final temperature of 900°C at a heating rate of 5°C / min, and then increased to a final temperature of 1300°C at a heating rate of 1°C / min. After constant temperature reaction for 2 hours, the temperature was cooled to room temperature at a cooling rate of 2°C / min to obtain a high-temperature calcined precursor.
[0059] S5. Place the high-temperature calcined precursor in a rotary tube furnace, introduce protective gas argon at a flow rate of 60 mL / min, increase the temperature to 800 °C at a rate of 5 °C / min, introduce active gas acetylene at a flow rate of 28 mL / min for chemical vapor deposition, stay for 30 minutes, stop introducing acetylene gas, keep the reaction warm for 90 minutes, then cool to room temperature at a rate of 5 °C / min to obtain a hard carbon negative electrode material. Example 2
[0060] S1. The waste beech wood is cleaned, dried, crushed and sieved to obtain a pre-treated precursor;
[0061] S2. The obtained pre-treated precursor was placed in a tubular furnace for low-temperature pyrolysis pre-treatment, and a protective gas argon gas with a flow rate of 60 mL / min was introduced, and the temperature was increased to 300 °C at a heating rate of 5 °C / min, and then the temperature was increased to a final temperature of 600 °C at a rate of 1 °C / min. After isothermal reaction for 2 hours, the temperature was cooled to room temperature at a cooling rate of 5 °C / min to obtain a pre-treated precursor;
[0062] S3. Soak the pretreated precursor in 1M / L hydrochloric acid solution for 24 hours, then wash with deionized water until the pH is 7, and finally dry it in a vacuum oven to obtain a clean pretreated precursor.
[0063] S4. The clean pretreated precursor was placed in a high-temperature tube furnace for high-temperature calcination, and a protective gas argon gas was introduced at a flow rate of 60 mL / min. The temperature was increased to a final temperature of 900°C at a heating rate of 5°C / min, and then increased to a final temperature of 1300°C at a heating rate of 1°C / min. After constant temperature reaction for 2 hours, the temperature was cooled to room temperature at a cooling rate of 2°C / min to obtain a high-temperature calcined precursor.
[0064] S5. Place the high-temperature calcined precursor in a rotary tube furnace, introduce protective gas argon at a flow rate of 60 mL / min, increase the temperature to 750 °C at a rate of 5 °C / min, introduce active gas acetylene at a flow rate of 28 mL / min for chemical vapor deposition, stay for 30 minutes, stop introducing acetylene gas, keep the temperature for reaction for 90 minutes, then cool down to room temperature at a rate of 5 °C / min to obtain a hard carbon negative electrode material. Example 3
[0065] S1. The waste beech wood is cleaned, dried, crushed and sieved to obtain a pre-treated precursor;
[0066] S2. The obtained pre-treated precursor was placed in a tubular furnace for low-temperature pyrolysis pre-treatment, and a protective gas argon gas with a flow rate of 60 mL / min was introduced, and the temperature was increased to 300 °C at a heating rate of 5 °C / min, and then the temperature was increased to a final temperature of 600 °C at a rate of 1 °C / min. After isothermal reaction for 2 hours, the temperature was cooled to room temperature at a cooling rate of 5 °C / min to obtain a pre-treated precursor;
[0067] S3. Soak the pretreated precursor in 1M / L hydrochloric acid solution for 24 hours, then wash with deionized water until the pH is 7, and finally dry it in a vacuum oven to obtain a clean pretreated precursor.
[0068] S4. The clean pretreated precursor was placed in a high-temperature tube furnace for high-temperature calcination, and a protective gas argon gas was introduced at a flow rate of 60 mL / min. The temperature was increased to a final temperature of 900°C at a heating rate of 5°C / min, and then increased to a final temperature of 1300°C at a heating rate of 1°C / min. After constant temperature reaction for 2 hours, the temperature was cooled to room temperature at a cooling rate of 2°C / min to obtain a high-temperature calcined precursor.
[0069] S5. Place the high-temperature calcined precursor in a rotary tube furnace, introduce protective gas argon at a flow rate of 60 mL / min, increase the temperature to 800 °C at a rate of 5 °C / min, introduce active gas acetylene at a flow rate of 28 mL / min for chemical vapor deposition, stay for 60 minutes, stop introducing acetylene gas, keep the temperature for 90 minutes, then cool to room temperature at a rate of 5 °C / min to obtain a hard carbon negative electrode material. Example 4
[0070] S1. The waste beech wood is cleaned, dried, crushed and sieved to obtain a pre-treated precursor;
[0071] S2. The obtained pre-treated precursor was placed in a tubular furnace for low-temperature pyrolysis pre-treatment, and a protective gas argon gas with a flow rate of 60 mL / min was introduced, and the temperature was increased to 300 °C at a heating rate of 5 °C / min, and then the temperature was increased to a final temperature of 600 °C at a rate of 1 °C / min. After isothermal reaction for 2 hours, the temperature was cooled to room temperature at a cooling rate of 5 °C / min to obtain a pre-treated precursor;
[0072] S3. Soak the pretreated precursor in 1M / L hydrochloric acid solution for 24 hours, then wash with deionized water until the pH is 7, and finally dry it in a vacuum oven to obtain a clean pretreated precursor.
[0073] S4. The clean pretreated precursor was placed in a high-temperature tube furnace for high-temperature calcination, and a protective gas argon gas was introduced at a flow rate of 60 mL / min. The temperature was increased to a final temperature of 900°C at a heating rate of 5°C / min, and then increased to a final temperature of 1300°C at a heating rate of 1°C / min. After constant temperature reaction for 2 hours, the temperature was cooled to room temperature at a cooling rate of 2°C / min to obtain a high-temperature calcined precursor.
[0074] S5. Place the high-temperature calcined precursor in a rotary tube furnace, introduce protective gas argon at a flow rate of 60 mL / min, increase the temperature to 800 °C at a rate of 5 °C / min, introduce active gas acetylene at a flow rate of 28 mL / min for chemical vapor deposition, stay for 120 minutes, stop introducing acetylene gas, keep the temperature for reaction for 90 minutes, then cool to room temperature at a rate of 5 °C / min to obtain a hard carbon negative electrode material. Example 5
[0075] S1. The waste beech wood is cleaned, dried, crushed and sieved to obtain a pre-treated precursor;
[0076] S2. The obtained pre-treated precursor was placed in a tubular furnace for low-temperature pyrolysis pre-treatment, and a protective gas argon gas with a flow rate of 60 mL / min was introduced, and the temperature was increased to 300 °C at a heating rate of 15 °C / min, and then the temperature was increased to a final temperature of 600 °C at a rate of 1 °C / min. After isothermal reaction for 2 hours, the temperature was cooled to room temperature at a cooling rate of 5 °C / min to obtain a pre-treated precursor;
[0077] S3. Soak the pretreated precursor in 1M / L hydrochloric acid solution for 24 hours, then wash with deionized water until the pH is 7, and finally dry it in a vacuum oven to obtain a clean pretreated precursor.
[0078] S4. The clean pretreated precursor was placed in a high-temperature tube furnace for high-temperature calcination, and a protective gas argon gas was introduced at a flow rate of 60 mL / min. The temperature was increased to a final temperature of 900°C at a heating rate of 5°C / min, and then increased to a final temperature of 1300°C at a heating rate of 1°C / min. After constant temperature reaction for 2 hours, the temperature was cooled to room temperature at a cooling rate of 2°C / min to obtain a high-temperature calcined precursor.
[0079] S5. Place the high-temperature calcined precursor in a rotary tube furnace, introduce protective gas argon at a flow rate of 60 mL / min, increase the temperature to 800 °C at a rate of 5 °C / min, introduce active gas acetylene at a flow rate of 28 mL / min for chemical vapor deposition, stay for 30 minutes, stop introducing acetylene gas, keep the reaction warm for 90 minutes, then cool to room temperature at a rate of 5 °C / min to obtain a hard carbon negative electrode material. Example 6
[0080] S1. The waste beech wood is cleaned, dried, crushed and sieved to obtain a pre-treated precursor;
[0081] S2. The obtained pretreated precursor was placed in a tubular furnace for low-temperature pyrolysis pretreatment, and a protective gas argon gas with a flow rate of 60 mL / min was introduced, and the temperature was raised to a final temperature of 600 °C at a rate of 5 °C / min. After isothermal reaction for 2 hours, the temperature was lowered to room temperature at a rate of 5 °C / min to obtain a pretreated precursor;
[0082] S3. Soak the pretreated precursor in 1M / L hydrochloric acid solution for 24 hours, then wash with deionized water until the pH is 7, and finally dry it in a vacuum oven to obtain a clean pretreated precursor.
[0083] S4. The clean pretreated precursor was placed in a high-temperature tube furnace for high-temperature calcination, and a protective gas argon gas was introduced at a flow rate of 60 mL / min. The temperature was increased to a final temperature of 900°C at a heating rate of 5°C / min, and then increased to a final temperature of 1300°C at a heating rate of 1°C / min. After constant temperature reaction for 2 hours, the temperature was cooled to room temperature at a cooling rate of 2°C / min to obtain a high-temperature calcined precursor.
[0084] S5. Place the high-temperature calcined precursor in a rotary tube furnace, introduce protective gas argon at a flow rate of 60 mL / min, increase the temperature to 800 °C at a rate of 5 °C / min, introduce active gas acetylene at a flow rate of 28 mL / min for chemical vapor deposition, stay for 30 minutes, stop introducing acetylene gas, keep the reaction warm for 90 minutes, then cool to room temperature at a rate of 5 °C / min to obtain a hard carbon negative electrode material. Example 7
[0085] S1. The waste beech wood is cleaned, dried, crushed and sieved to obtain a pre-treated precursor;
[0086] S2. The obtained pre-treated precursor was placed in a tubular furnace for low-temperature pyrolysis pre-treatment, and a protective gas argon gas with a flow rate of 5 mL / min was introduced, and the temperature was increased to 300 °C at a heating rate of 5 °C / min, and then the temperature was increased to a final temperature of 600 °C at a rate of 1 °C / min. After isothermal reaction for 2 hours, the temperature was cooled to room temperature at a cooling rate of 5 °C / min to obtain a pre-treated precursor;
[0087] S3. Soak the pretreated precursor in 1M / L hydrochloric acid solution for 24 hours, then wash with deionized water until the pH is 7, and finally dry it in a vacuum oven to obtain a clean pretreated precursor.
[0088] S4. The clean pretreated precursor was placed in a high-temperature tube furnace for high-temperature calcination, and a protective gas argon gas was introduced at a flow rate of 60 mL / min. The temperature was increased to a final temperature of 900°C at a heating rate of 5°C / min, and then increased to a final temperature of 1300°C at a heating rate of 1°C / min. After constant temperature reaction for 2 hours, the temperature was cooled to room temperature at a cooling rate of 2°C / min to obtain a high-temperature calcined precursor.
[0089] S5. Place the high-temperature calcined precursor in a rotary tube furnace, introduce protective gas argon at a flow rate of 60 mL / min, increase the temperature to 800 °C at a rate of 5 °C / min, introduce active gas acetylene at a flow rate of 28 mL / min for chemical vapor deposition, stay for 30 minutes, stop introducing acetylene gas, keep the reaction warm for 90 minutes, then cool to room temperature at a rate of 5 °C / min to obtain a hard carbon negative electrode material. Example 8
[0090] S1. The waste beech wood is cleaned, dried, crushed and sieved to obtain a pre-treated precursor;
[0091] S2. The obtained pre-treated precursor was placed in a tubular furnace for low-temperature pyrolysis pre-treatment, and a protective gas argon gas with a flow rate of 60 mL / min was introduced, and the temperature was increased to 300 °C at a heating rate of 5 °C / min, and then the temperature was increased to a final temperature of 600 °C at a rate of 1 °C / min. After isothermal reaction for 2 hours, the temperature was cooled to room temperature at a cooling rate of 5 °C / min to obtain a pre-treated precursor;
[0092] S3. The pretreated precursor was soaked in 0.1M / L hydrochloric acid solution for 24h, then washed with deionized water until the pH was 7, and finally dried in a vacuum oven to obtain a clean pretreated precursor;
[0093] S4: The clean pretreated precursor was placed in a high-temperature tube furnace for high-temperature calcination, and a protective gas argon gas was introduced at a flow rate of 60 mL / min. The temperature was increased to a final temperature of 900°C at a heating rate of 5°C / min, and then increased to a final temperature of 1300°C at a heating rate of 1°C / min. After constant temperature reaction for 2 hours, the temperature was cooled to room temperature at a cooling rate of 2°C / min to obtain a high-temperature calcined precursor.
[0094] S5
[0095] .The high-temperature calcined precursor was placed in a rotary tube furnace, and a protective gas argon gas was introduced at a flow rate of 60 mL / min. The temperature was raised to 800 °C at a rate of 5 °C / min. The active gas acetylene was introduced at a flow rate of 28 mL / min for chemical vapor deposition. After staying for 30 minutes, the acetylene gas was stopped. After the reaction was kept warm for 90 minutes, the temperature was lowered to room temperature at a rate of 5 °C / min to obtain a hard carbon negative electrode material. Example 9
[0096] S1. The waste beech wood is cleaned, dried, crushed and sieved to obtain a pre-treated precursor;
[0097] S2. The obtained pre-treated precursor was placed in a tubular furnace for low-temperature pyrolysis pre-treatment, and a protective gas argon gas with a flow rate of 60 mL / min was introduced, and the temperature was increased to 300 °C at a heating rate of 5 °C / min, and then the temperature was increased to a final temperature of 600 °C at a rate of 1 °C / min. After isothermal reaction for 2 hours, the temperature was cooled to room temperature at a cooling rate of 5 °C / min to obtain a pre-treated precursor;
[0098] S3. Soak the pretreated precursor in 1M / L hydrochloric acid solution for 24 hours, then wash with deionized water until the pH is 7, and finally dry it in a vacuum oven to obtain a clean pretreated precursor.
[0099] S4. The clean pretreated precursor is placed in a high-temperature tube furnace for high-temperature calcination, and a protective gas argon is introduced at a flow rate of 60 mL / min. The temperature is increased to a final temperature of 600°C at a heating rate of 5°C / min, and then increased to a final temperature of 1300°C at a heating rate of 1°C / min. After constant temperature reaction for 2 hours, the temperature is cooled to room temperature at a cooling rate of 2°C / min to obtain a high-temperature calcined precursor.
[0100] S5. Place the high-temperature calcined precursor in a rotary tube furnace, introduce protective gas argon at a flow rate of 60 mL / min, increase the temperature to 800 °C at a rate of 5 °C / min, introduce active gas acetylene at a flow rate of 28 mL / min for chemical vapor deposition, stay for 30 minutes, stop introducing acetylene gas, keep the reaction warm for 90 minutes, then cool to room temperature at a rate of 5 °C / min to obtain a hard carbon negative electrode material.
[0101] Embodiment 10:
[0102] S1. The waste beech wood is cleaned, dried, crushed and sieved to obtain a pre-treated precursor;
[0103] S2. The obtained pre-treated precursor was placed in a tubular furnace for low-temperature pyrolysis pre-treatment, and a protective gas argon gas with a flow rate of 60 mL / min was introduced, and the temperature was increased to 300 °C at a heating rate of 5 °C / min, and then the temperature was increased to a final temperature of 600 °C at a rate of 1 °C / min. After isothermal reaction for 2 hours, the temperature was cooled to room temperature at a cooling rate of 5 °C / min to obtain a pre-treated precursor;
[0104] S3. The pretreated precursor was soaked in 1M / L hydrochloric acid solution for 24h, then washed with deionized water until the pH was 7, and finally dried in a vacuum oven to obtain a clean pretreated precursor;
[0105] The sodium bicarbonate-coated polyvinyl alcohol fiber prepared in Preparation Example 2 is electrostatically sprayed on the clean pre-treated precursor, and then dried to obtain a sodium bicarbonate spray precursor.
[0106] S4. The sodium bicarbonate spray precursor was placed in a high-temperature tubular furnace for high-temperature calcination. A protective gas argon gas was introduced at a flow rate of 60 mL / min. The temperature was increased to a final temperature of 900°C at a heating rate of 5°C / min, and then increased to a final temperature of 1300°C at a heating rate of 1°C / min. After constant temperature reaction for 2 hours, the temperature was cooled to room temperature at a cooling rate of 2°C / min to obtain a high-temperature calcined precursor.
[0107] S5. Place the high-temperature calcined precursor in a rotary tube furnace, introduce protective gas argon at a flow rate of 60 mL / min, increase the temperature to 800 °C at a rate of 5 °C / min, introduce active gas acetylene at a flow rate of 28 mL / min for chemical vapor deposition, stay for 30 minutes, stop introducing acetylene gas, keep the reaction warm for 90 minutes, then cool to room temperature at a rate of 5 °C / min to obtain a hard carbon negative electrode material.
[0108] Embodiment 11:
[0109] S1. The waste beech wood is cleaned, dried, crushed and sieved to obtain a pre-treated precursor;
[0110] S2. The obtained pre-treated precursor was placed in a tubular furnace for low-temperature pyrolysis pre-treatment, and a protective gas argon gas with a flow rate of 60 mL / min was introduced, and the temperature was increased to 300 °C at a heating rate of 5 °C / min, and then the temperature was increased to a final temperature of 600 °C at a rate of 1 °C / min. After isothermal reaction for 2 hours, the temperature was cooled to room temperature at a cooling rate of 5 °C / min to obtain a pre-treated precursor;
[0111] S3. The pretreated precursor was soaked in 1M / L hydrochloric acid solution for 24h, then washed with deionized water until the pH was 7, and finally dried in a vacuum oven to obtain a clean pretreated precursor;
[0112] The sodium bicarbonate-coated polyvinyl alcohol fiber prepared in Preparation Example 3 is electrostatically sprayed on the clean pre-treated precursor, and then dried to obtain a sodium bicarbonate spray precursor.
[0113] S4. The sodium bicarbonate spray precursor was placed in a high-temperature tubular furnace for high-temperature calcination. A protective gas argon gas was introduced at a flow rate of 60 mL / min. The temperature was increased to a final temperature of 900°C at a heating rate of 5°C / min, and then increased to a final temperature of 1300°C at a heating rate of 1°C / min. After constant temperature reaction for 2 hours, the temperature was cooled to room temperature at a cooling rate of 2°C / min to obtain a high-temperature calcined precursor.
[0114] S5. Place the high-temperature calcined precursor in a rotary tube furnace, introduce protective gas argon at a flow rate of 60 mL / min, increase the temperature to 800 °C at a rate of 5 °C / min, introduce active gas acetylene at a flow rate of 28 mL / min for chemical vapor deposition, stay for 30 minutes, stop introducing acetylene gas, keep the reaction warm for 90 minutes, then cool to room temperature at a rate of 5 °C / min to obtain a hard carbon negative electrode material.
[0115] Embodiment 12:
[0116] S1. The waste beech wood is cleaned, dried, crushed and sieved to obtain a pre-treated precursor;
[0117] S2. The obtained pre-treated precursor was placed in a tubular furnace for low-temperature pyrolysis pre-treatment, and a protective gas argon gas with a flow rate of 60 mL / min was introduced, and the temperature was increased to 300 °C at a heating rate of 5 °C / min, and then the temperature was increased to a final temperature of 600 °C at a rate of 1 °C / min. After isothermal reaction for 2 hours, the temperature was cooled to room temperature at a cooling rate of 5 °C / min to obtain a pre-treated precursor;
[0118] S3. The pretreated precursor was soaked in 1M / L hydrochloric acid solution for 24h, then washed with deionized water until the pH was 7, and finally dried in a vacuum oven to obtain a clean pretreated precursor;
[0119] The sodium bicarbonate-coated polyvinyl alcohol fiber prepared in Preparation Example 4 is electrostatically sprayed on the clean pre-treated precursor, and then dried to obtain a sodium bicarbonate spray precursor.
[0120] S4. The sodium bicarbonate spray precursor was placed in a high-temperature tubular furnace for high-temperature calcination. A protective gas argon gas was introduced at a flow rate of 60 mL / min. The temperature was increased to a final temperature of 900°C at a heating rate of 5°C / min, and then increased to a final temperature of 1300°C at a heating rate of 1°C / min. After constant temperature reaction for 2 hours, the temperature was cooled to room temperature at a cooling rate of 2°C / min to obtain a high-temperature calcined precursor.
[0121] S5. Place the high-temperature calcined precursor in a rotary tube furnace, introduce protective gas argon at a flow rate of 60 mL / min, increase the temperature to 800 °C at a rate of 5 °C / min, introduce active gas acetylene at a flow rate of 28 mL / min for chemical vapor deposition, stay for 30 minutes, stop introducing acetylene gas, keep the reaction warm for 90 minutes, then cool to room temperature at a rate of 5 °C / min to obtain a hard carbon negative electrode material.
[0122] Comparative Example
[0123] Comparative Example 1
[0124] S1. The waste beech wood is cleaned, dried, crushed and sieved to obtain a pre-treated precursor;
[0125] S2. The obtained pre-treated precursor was placed in a tubular furnace for low-temperature pyrolysis pre-treatment, and a protective gas argon gas with a flow rate of 60 mL / min was introduced, and the temperature was increased to 300 °C at a heating rate of 5 °C / min, and then the temperature was increased to a final temperature of 600 °C at a rate of 1 °C / min. After isothermal reaction for 2 hours, the temperature was cooled to room temperature at a cooling rate of 5 °C / min to obtain a pre-treated precursor;
[0126] S3. Soak the pretreated precursor in 1M / L hydrochloric acid solution for 24 hours, then wash with deionized water until the pH is 7, and finally dry it in a vacuum oven to obtain a clean pretreated precursor.
[0127] S4. The clean pretreated precursor was placed in a high-temperature tubular furnace for high-temperature calcination, and argon protective gas was introduced at a flow rate of 60 mL / min. The temperature was increased to a final temperature of 900°C at a heating rate of 5°C / min, and then increased to a final temperature of 1300°C at a heating rate of 1°C / min. After constant temperature reaction for 2 hours, the temperature was cooled to room temperature at a cooling rate of 2°C / min to obtain a hard carbon negative electrode material.
[0128] Comparative Example 2
[0129] S1. The phenolic resin is washed, dried, crushed and sieved to obtain a pretreated precursor;
[0130] S2. The obtained pre-treated precursor was placed in a tubular furnace for low-temperature pyrolysis pre-treatment, and a protective gas argon gas with a flow rate of 60 mL / min was introduced, and the temperature was increased to 300 °C at a heating rate of 5 °C / min, and then the temperature was increased to a final temperature of 600 °C at a rate of 1 °C / min. After isothermal reaction for 2 hours, the temperature was cooled to room temperature at a cooling rate of 5 °C / min to obtain a pre-treated precursor;
[0131] S3. Soak the pretreated precursor in 1M / L hydrochloric acid solution for 24 hours, then wash with deionized water until the pH is 7, and finally dry it in a vacuum oven to obtain a clean pretreated precursor.
[0132] S4. The clean pretreated precursor was placed in a high-temperature tube furnace for high-temperature calcination, and a protective gas argon gas was introduced at a flow rate of 60 mL / min. The temperature was increased to a final temperature of 900°C at a heating rate of 5°C / min, and then increased to a final temperature of 1300°C at a heating rate of 1°C / min. After constant temperature reaction for 2 hours, the temperature was cooled to room temperature at a cooling rate of 2°C / min to obtain a high-temperature calcined precursor.
[0133] S5. Place the high-temperature calcined precursor in a rotary tube furnace, introduce protective gas argon at a flow rate of 60 mL / min, increase the temperature to 800 °C at a rate of 5 °C / min, introduce active gas acetylene at a flow rate of 28 mL / min for chemical vapor deposition, stay for 30 minutes, stop introducing acetylene gas, keep the reaction warm for 90 minutes, then cool to room temperature at a rate of 5 °C / min to obtain a hard carbon negative electrode material.
[0134] Performance testing
[0135] The specific capacity (mAh / g) and the first coulomb efficiency (%) of the hard carbon negative electrode materials prepared in each embodiment and comparative example were tested. The negative electrode material was charged to 4.0V at a constant current of 1C, then charged at a constant voltage to a current of 0.05C, and then discharged to 2.0V at a constant current of 1C, and the capacity retention rate (%) was tested after 100 cycles. The test results are summarized in Table 1.
[0136] Table 1
[0137] Specific capacity (mAh / g) First coulombic efficiency (%) Capacity retention rate (%) Example 1 349.0 79.24 91.2 Example 2 347.5 78.11 91.1 Example 3 340.7 79.97 91.1 Example 4 337.9 78.47 90.5 Example 5 308.9 77.41 89.8 Example 6 301.18 75.42 87.4 Example 7 302.21 75.43 84.8 Example 8 343.7 78.01 90.1 Example 9 304.7 75.11 87.9 Example 10 351.6 81.21 91.3 Embodiment 11 354.2 81.7 91.3 Example 12 360.1 82.1 91.4 Comparative Example 1 254.4 56.47 78.8 Comparative Example 2 277.1 46.38 84.38
[0138] The SEM image of the hard carbon negative electrode material provided in Example 1 is as follows Figure 1 As shown, it can be seen that the prepared negative electrode material shows a typical granular morphology with different particle sizes.
[0139] The TEM image of the hard carbon negative electrode material provided in Example 1 is as follows Figure 2 As shown, it can be seen that the sample has ordered regions and abundant pores.
[0140] The nitrogen adsorption-desorption curve of the hard carbon negative electrode material provided in Example 1 is as follows: Figure 3 As shown, it can be seen that the specific surface area of the prepared hard carbon negative electrode material is 84.6 m² / g, indicating that the pores of the prepared negative electrode material have a large specific surface area and are rich in open nanopores.
[0141] The pore size distribution curve of the hard carbon negative electrode material provided in Example 1 is as follows: Figure 4 As shown, it can be seen that the negative electrode material has a large number of micropores and mesopores, a large number of mesopores are conducive to the rapid diffusion of sodium ions, and a large number of micropores are conducive to the storage of sodium ions.
[0142] The first cycle charge and discharge curve of the hard carbon negative electrode material provided in Example 1 is as follows Figure 5 As shown, it can be seen that the prepared hard carbon negative electrode material has a first coulombic efficiency of up to 79.24%, a reversible specific capacity of up to 349.0 mAh / g, and a low potential platform specific capacity of 201 mAh / g.
[0143] In combination with Example 1, Comparative Examples 1-2 and Table 1, the present application uses waste wood carbonization and chemical vapor deposition (CVD) as the negative electrode material, and limits the parameters of each step. The hard carbon negative electrode material obtained has a uniform and stable pore distribution, is not easy to shrink and expand after the sodium ions are released and embedded, has high specific capacity and first coulombic efficiency, and has good cycle performance.
[0144] In combination with Examples 1-4 and Table 1, the present application limits the temperature of the chemical vapor deposition process and the residence time of the active gas, so that the surface of the hard carbon negative electrode material obtained has a dense and uniform carbon coating layer, uniform particle size, many closed pores, high specific capacity and first coulombic efficiency, and good cycle performance.
[0145] In combination with Example 1, Examples 5-7 and Table 1, the present application limits the heating rate and the flow rate of the protective gas in the low-temperature cracking process, so that the hard carbon negative electrode material obtained has good cracking effect and a uniform and stable structure.
[0146] In combination with Example 1 and Example 8 and Table 1, the present application performs acid washing of a certain concentration on the pre-treated precursor, so that less inorganic impurities remain after cracking, and the prepared hard carbon negative electrode material is more stable.
[0147] In combination with Example 1 and Example 9 and Table 1, the present application limits the temperature of the carbonization process, so that the hard carbon negative electrode material obtained has good carbonization effect, high specific capacity and first coulombic efficiency, and good cycle performance.
[0148] In combination with Example 1, Examples 10-12 and Table 1, the present application further increases the number of micropores and mesopores and optimizes the long-range closed-pore structure by spraying sodium bicarbonate-coated polyvinyl alcohol fibers on the surface of the clean pretreated precursor. The hard carbon negative electrode material obtained has good carbonization effect, and has good performance in specific capacity, first coulomb efficiency and capacity retention rate.
[0149] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A cheap, high-performance hard carbon negative electrode material for sodium ion secondary batteries, characterized in that: The preparation process of the negative electrode material comprises the following steps: S1. Washing, drying, crushing and screening the waste wood to obtain a clean precursor; S2. performing low temperature pyrolysis pretreatment on the clean precursor to obtain a pretreated precursor; S3. The pretreated precursor is washed and dried to obtain a clean pretreated precursor; S4. Carbonization preparation: The clean pretreated precursor prepared in S3 is placed in a high temperature tube furnace for high temperature calcination, a protective gas is introduced, the temperature is gradually raised to the final temperature, and then the reaction is carried out at a constant temperature. After the reaction is completed, the temperature is gradually lowered to room temperature to obtain a high temperature calcined precursor; S5. Chemical vapor deposition: The high-temperature calcined precursor is placed in a rotary tube furnace, a protective gas is introduced, and the temperature is gradually raised to a specific temperature, and a highly reactive gas is introduced, and then the introduction of the reactive gas is stopped, and the reaction is carried out at a constant temperature. After the reaction is completed, the temperature is gradually lowered to room temperature to obtain a hard carbon negative electrode material; The S3 further comprises the following steps: mixing polyvinyl alcohol, butanediol, glycerol, sulfonate polyether diol, sodium dodecylbenzene sulfonate and deionized water, stirring evenly, then adding sodium bicarbonate and sodium bicarbonate microcapsules, stirring evenly to obtain a mixture, adding the mixture and polyvinyl alcohol fiber to a coating machine to obtain sodium bicarbonate-coated polyvinyl alcohol fiber; electrostatically spraying the obtained sodium bicarbonate-coated polyvinyl alcohol fiber on the clean pretreatment precursor, and drying; The preparation steps of the sodium bicarbonate microcapsule include: mixing sodium bicarbonate, epoxy resin and anhydrous ethanol evenly, adding triethylenetetramine and sodium dodecylbenzene sulfonate, stirring evenly, heating for reaction, filtering, washing and drying to obtain the sodium bicarbonate microcapsule.
2. A cheap, high-performance hard carbon negative electrode material for sodium ion secondary batteries according to claim 1, characterized in that: The preparation steps of low temperature cracking in S2 include: placing a clean precursor into a high temperature tubular furnace for calcination, introducing a protective gas, gradually heating up to a final temperature, then reacting at a constant temperature, and gradually cooling down to room temperature after the reaction is completed.
3. A cheap, high-performance hard carbon negative electrode material for sodium ion secondary batteries according to claim 2, characterized in that: The temperature in the preparation step of low temperature cracking in S2 is first increased to 250-350°C at a rate of 0.5-10°C / min, then increased to a final temperature of 500-800°C at 0.5-4°C / min, the constant temperature time is 0.5-8 h, and the cooling rate is 0.1-10°C / min.
4. A cheap, high-performance hard carbon negative electrode material for sodium ion secondary batteries according to claim 2, characterized in that: The protective gas in the preparation step of low-temperature cracking in S2 includes one or more of argon or nitrogen, and the flow rate of the protective gas is 10-100 mL / min.
5. A cheap, high-performance hard carbon negative electrode material for sodium ion secondary batteries according to claim 1, characterized in that: The cleaning in S3 is 0.2-2 M concentration acid cleaning, and the acid includes one or more of hydrochloric acid, nitric acid, and sulfuric acid.
6. A cheap, high-performance hard carbon negative electrode material for sodium ion secondary batteries according to claim 1, characterized in that: In S4, the heating rate is 0.5-10°C / min, the final temperature is 700-1600°C, the constant temperature time is 0.5-8 h, and the cooling rate is 0.1-10°C / min.
7. The low-cost, high-performance hard carbon negative electrode material for sodium ion secondary batteries according to claim 1, characterized in that: The protective gas in S4 includes one or more of argon or nitrogen, and the flow rate of the protective gas is 10-100 mL / min.
8. The low-cost, high-performance hard carbon negative electrode material for sodium ion secondary batteries according to claim 1, characterized in that: The highly reactive gas in S5 is acetylene with a flow rate of 28-100 mL / min, and the protective gas includes one or more of argon or nitrogen with a flow rate of 28-100 mL / min.
9. The low-cost, high-performance hard carbon negative electrode material for sodium ion secondary batteries according to claim 1, characterized in that: The heating rate in S5 is 5-10°C / min, the final temperature is 700-900°C, the time for introducing highly reactive gas is 0.5-2h, the constant temperature time is 0.4-6h, and the cooling rate is 5-10°C / min.
Citation Information
Patent Citations
Hard carbon negative electrode material for sodium ion battery and preparation method of hard carbon negative electrode material
CN116169238A